Enfisema subcutáneo en tórax en paciente de sexo masculino de 50 años de edad. - Burbano Monserrate, Axelle Noemy (2020)
Subcutaneous emphysema is considered a type of chronic obstructive pulmonary disease (COPD), it leads to the destruction of lung tissue and leaving air trapped within it. The problem is that this air that gradually stays inside the lungs, specifically in the alveoli, makes breathing even more difficult because they enlarge and the diaphragm flattens. This makes the inhalation and exhalation movement of moving air in and out of the lungs difficult..Some of the most relevant clinical manifestations are swelling and chest pain, swallowing problems, slight sounds when breathing, and choking. For the proper diagnosis, the clinical history and the respective complementary examinations of the patient are analyzed, imaging studies such as chest x-rays and computed tomography are made. The objective of this study is for the 50-year-old patient with subcutaneous emphysema in the chest to know the appropriate treatment.